Multicultural Relationship of Chinese Ethnic With Sundanese Ethnic in Cibadak Chinatown, Bandung City - Alventia, Ester (International Journal Pedagogy of Social Studies, 2023)
This research is motivated by not running smoothly inter-ethnic assimilation in Indonesia. Thus, this study aims to obtain an overview of the multicultural relations between the Chinese and the Sundanese in Cibadak Chinatown, Bandung City. The research was carried out using a qualitative approach, with a descriptive study method, by obtaining data through documentation studies, interviews, observations, and literature studies. The results of this study indicate that 1) the adaptations carried out by the Chinese ethnicity with the Sundanese ethnicity in the Chinatown of Cibadak, Bandung City include the dimensions of language, namely Indonesian and Sundanese, descent (marriage) between ethnic Chinese and Sundanese, and street naming using accents. Chinese. 2) The purpose of carrying out multicultural relations by ethnic Chinese and ethnic Sundanese because of the motive for carrying out trade expansion and looking for a safe place so that ethnic Chinese can maintain their culture and religion in Cibadak Chinatown, Bandung City. 3) Integration carried out by ethnic Chinese and ethnic Sundanese in Chinatown Cibadak, Bandung City, including through cultural activities of Barongshai, Liong, Cepot, Sisingaan, Degungan, and Pencak Silat. Meanwhile, in religious activities, there are religious activities for Thanksgiving Night, Breaking Together, Worshiping King Siliwangi, and Ce It Cap Go. 4) Pattern maintenance in an effort to equip and improve multicultural relations is strongly influenced by religious leaders, community leaders, and norms that apply in the Chinatown of Cibadak, Bandung City, which administratively is located in Cibadak Village, Bandung City.